Growth and Properties of (Yb-Er) Co-Doped ZnO Thin Films Deposited via Spray Pyrolysis Technique - Abderrahim El Hat; Imane Chaki; Rida Essajai; Abdelmajid Fakhim Lamrani; Boubker Fares; Mohammed Regragui; Aziz Dinia; Mohammed Abd-Lefdil (Optics)
YbxEryZnO thin films with a low concentration (x = 5%, y = 0, 1, 3%) were made on glass substrates using the spray pyrolysis method. The films were characterized through the use of specific techniques to investigate their structural, optical, and electrical properties. The XRD structural analysis of the films revealed that they are polycrystalline with a hexagonal wurtzite structure and a preferential orientation in the (002) direction. The optical characterization of the co-doped layers in the range of 200 to 800 nm revealed that co-doping had a significant impact on the values of transmission. A well-defined peak in the infrared domain centered around 980 nm was observed in photoluminescence measurements. This peak signifies the transition between the electronic levels 2F5/2 (ground state) and 2F7/2 (excited state), proving that photons are efficiently transferred between the ZnO matrix and the Yb3+ ion. All layers exhibited n-type conduction and an electrical resistivity decrease to 6.0 × 10−2 Ω cm according to Hall effect measurements at room temperature.